Brand Image Mediates Product Quality, Promotion Towards Purchasing Decisions (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The purpose of this research is to examine and analyze the influence of product quality and promotion on purchasing decisions through brand image at UD. Woodgrand in Jepara. The data collection method used in this study was a questionnaire distributed via Google Form to eligible respondents. It was then processed using Smart PLS version 4 with a total of 99 respondents. The novelty in this study lies in the different research locations or sites, resulting in varying results. The results indicate that product quality influences purchasing decisions, promotion influences purchasing decisions, product quality influences brand image, promotion influences brand image, and brand image influences purchasing decisions. Therefore, it can be concluded that product quality, promotion, brand image, and purchasing decisions are interrelated. Meanwhile, brand image, as a mediating variable, mediates the relationship between product quality and purchasing decisions, and promotion influences purchasing decisions.
Keywords: Product Quality; Promotion; Brand Image; Purchasing Decisions